Did History Breed Inequality? Colonial Factor Endowments and Modern Income Distribution - Matthew J. Baker; Christa N. Brunnschweiler; Erwin H. Bulte (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
We explore the relation between historical population density in former colonies and modern income distribution. A theoretical model highlights the potentially opposing effects of native population density on incentives for colonists to conquer or settle in new territories. While an abundant supply of native labor is an “asset” that drives up land rents, it is also a “liability” that makes land acquisition by colonists more difficult and reduces returns to peacable migration. Conflicts over land, sowing the seeds for inequality by creating a landed élite living off rents, are especially likely to emerge for intermediate native population densities. Results are confirmed by detailed empirical tests highlighting the curvilinear relationship between native population density and modern income inequality. Finally, using population density as an instrument for inequality in the former colonies, we demonstrate that there is no causal relationship running from income distribution to economic growth.
Keywords: O15; N30; N50; 330; inequality; growth; factor endowments; population density; conflict; colonization; Bevölkerungsdichte; Indigene Völker; Kolonialismus; Einkommensverteilung; Wirtschaftswachstum; Welt